IMPLEMENTATION OF THE PROJECT BASED LEARNING (PJBL) LEARNING MODEL TO IMPROVE ELEMENTARY SCHOOL STUDENTS' SCIENCE LEARNING OUTCOMES - Atika Fauziah (Teaching and General Education Studies, 2026)
Science learning in elementary schools often faces challenges related to low student engagement and suboptimal learning outcomes, particularly when instruction relies on teacher-cantered approaches. Therefore, innovative learning models that actively involve students are required. This classroom action research aims to determine whether the Project-Based Learning (PjBL) model can improve science learning outcomes in fifth-grade students at SDN 6 Srikaton. The study was conducted using a classroom action research design consisting of two cycles. Data were collected through observation, learning outcome tests, and documentation. The results indicate that the implementation of the PjBL model effectively improved students’ science learning outcomes. Student mastery increased from 28.5% in the pre-cycle stage to 50% in Cycle I, and further rose to 78% of students achieving mastery in Cycle II. These findings demonstrate a consistent improvement in learning outcomes across cycles. This study concludes that the Project-Based Learning model is effective in enhancing science learning outcomes among fifth-grade elementary school students. The findings imply that teachers are encouraged to integrate PjBL into science instruction to promote active learning and deeper understanding. Future research is recommended to apply the PjBL model in different subjects, grade levels, or longer implementation periods to examine its broader impact on students’ skills and learning achievement.